Pathogenic genes implicated in sleep-related hypermotor epilepsy: a research progress update - Yang, Yufang; Tuo, Jinmei; Zhang, Jun; Xu, Zucai; Luo, Zhong (Frontiers in Neurology, 2024)
Sleep-related hypermotor epilepsy (SHE) is a focal epilepsy syndrome characterized by a variable age of onset and heterogeneous etiology. Current literature suggests a prevalence rate of approximately 1.8 per 100,000 persons. The discovery of additional pathogenic genes associated with SHE in recent years has significantly expanded the knowledge and understanding of its pathophysiological mechanisms. Identified SHE pathogenic genes include those related to neuronal ligand- and ion-gated channels (CHRNA4, CHRNB2, CHRNA2, GABRG2, and KCNT1), genes upstream of the mammalian target of rapamycin complex 1 signal transduction pathway (DEPDC5, NPRL2, NPRL3, TSC1, and TSC2), and other genes (CRH, CaBP4, STX1B and PRIMA1). These genes encode proteins associated with ion channels, neurotransmitter receptors, cell signal transduction, and synaptic transmission. Mutations in these genes can result in the dysregulation of encoded cellular functional proteins and downstream neuronal dysfunction, ultimately leading to epileptic seizures. However, the associations between most genes and the SHE phenotype remain unclear. This article presents a literature review on the research progress of SHE-related pathogenic genes to contribute evidence to genotype-phenotype correlations in SHE and establish the necessary theoretical basis for future SHE treatments.